A CRITICAL ANALYSIS OF ISLAM, ECONOMY AND FINANCE IN THE EARLY 21ST CENTURY - AHMAD MAULIDIZEN (Hukum Islam, 2017)
Belief system that can be received well by humans, either worldly (secular) and the hereafter (hereafter oriented) has two specific characteristics. These characteristics are: first, the belief system is flexible to adapt to different places and times, but still able to maintain the value of its authenticity. If not, the belief system will be destroyed or can be fused with other systems. The second characteristic, the system is ideal, sometimes even Utopian (fantasy), and is also able to set the imperfections of human and can be applied in human life, such as politics and economics. So we will have a better view on a system that originated from medieval times to survive and advance rapidly in the global economy. This article will discuss the history and evolution of religion, encompass about the mechanisms of Islam that is able to adapt to changing times, and the adaptation of Islam to the modern financial and economic system.